ANALISIS PENGARUH KINERJA LINGKUNGAN DAN BIAYA LINGKUNGAN TERHADAP PROFITABILITAS DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (PADA PERUSAHAAN SEKTOR INDUSTRI DAN KIMIA YANG TERDAFTAR DIBURSA EFEK INDONESIA PERIODE 2017-2020) - Hana Fahira; Yusrawati (Journal Of Islamic Finance And Accounting Research, 2023)
This study aims to determine and analyze the effect of environmental performance and environmental costs on profitability with firm size as a moderating variable in industrial and chemical sector companies listed on the Indonesia Stock Exchange for the 2017-2020 period. This research includes quantitative research using secondary data. The population in this study is the industrial and chemical sector companies listed on the Stock Exchange, with sampling using purposive sampling technique, which aims to obtain samples that match the research criteria. The sample used was 11 companies in the period 2017 to 2020. The data analysis techniques used were multiple regression analysis and moderated regression analysis (MRA). Based on the results of the tests that have been carried out, it shows that partially environmental performance has no effect on profitability, while environmental costs have an effect on profitability. Simultaneously, environmental performance variables, environmental costs, and firm size affect profitability. The moderating analysis of the firm size variable cannot moderate the relationship between environmental performance and profitability and the firm size variable cannot moderate the relationship between environmental costs and profitability.